Involvement of receptor-interacting protein 140 in palmitate-stimulated macrophage infiltration of pancreatic beta cells - Zou, Runmei (Exp Ther Med, 2017)
Receptor-interacting protein 140 (RIP140) in macrophages stimulates the nuclear factor-κB subunit RelA to activate tumor necrosis factor (TNF)-α and interleukin (IL)-6 transcription. However, under lipotoxic conditions, the involvement of RIP140 in the infiltration of beta cells by macrophages remains unknown. In the present study, murine RAW264.7 macrophages were transfected with a RIP140 overexpression plasmid or siRNA prior to macrophage activation with 500 µM palmitate. Palmitate-free conditioned media was then collected and added to murine insulinoma MIN6 cells. Significant decreases were observed in cell viability (P<0.01), glucose-stimulated insulin secretion (P<0.01) and levels of peroxisome proliferator-activated receptor-γ coactivator-1α (P<0.05), phosphoenolpyruvate carboxykinase and proliferating cell nuclear antigen mRNA (P<0.01) in MIN6 cells. In addition, conditioned media from palmitate-treated and RIP140-upregulated macrophages significantly increased the levels of uncoupling protein-2 (P<0.01), inducible nitric oxide synthase 1 (P<0.01) and pancreatic and duodenal homeobox 1 (P<0.05) mRNA and levels of activated Jun N-terminal kinase (JNK) (P<0.01) and extracellular signal-regulated kinase (ERK) 1/2 (P<0.01). In turn, the conditioned media was found to be significantly enriched in TNF-α and IL-6 (both P<0.05). These results were the opposite of those obtained from MIN6 cells treated with conditioned media from palmitate-treated and RIP140-knockdown macrophages. MIN6 cells were transfected with RIP140 overexpression plasmid or siRNA prior to treatment with 500 µM palmitate and supernatant was collected for use in macrophage chemotaxis assays. In the palmitate-activated and RIP140-overexpressing MIN6 cells, TNF-α and IL-6 secretion increased significantly (both P<0.05) and macrophage chemotaxis towards MIN6 cells was enhanced. By contrast, downregulating RIP140 in MIN6 cells had the opposite effect. These data suggest that RIP140 in macrophages mediates the transcription of inflammatory cytokines when concentration of palmitate is high. Macrophage RIP140 may also impair beta cell function by activating the JNK and ERK1/2 signaling pathways and promoting specific gene transcription. Furthermore, expression of RIP140 in pancreatic beta cells may stimulate macrophage chemotaxis, thus triggering local low-grade inflammation.